(untitled) (Progressive Agriculture, 2013)
The effect of barbados lilac (Melia azedarach, Linn., @100 mg/kg bwt. ), pineapple (Ananas comosus, Merr., @100mg/kg bwt.) and Benazol® (albendazole, @7.5 mg/kg bwt.) against natural gastrointestinal nematodes were studied in cattle. Their effect of TEC, Hb, PCV, TLC, ALT, AST and body weight were observed. Twenty four (24) naturally parasitized cattle of BAU Dairy Farm, Mymensingh were randomly divided into four groups, each consisting of six (6) cattle. Water extract of leaves of barbados lilac and pineapple were administered orally to the cattle of group A and B, respectively. Cattle of group C were treated with Benazol® orally. Cattle of group D was kept as infected control group. Fecal samples, body weight, hematological and biochemical parameters were examined before treatment and on 3rd, 10th, 17th and 28th day. A significant (p<0.01) reduction of EPG count was found following administration of barbados lilac (39.11-60.07%), pineapple (29.50-45.36%) and Benazol® (62.19-90.44%) in cattle. Whereas EPG increased significantly (p<0.01) in control group throughout the experimental period. After treatment with barbados lilac, pineapple and Benazol®, total erythrocyte count (TEC), hemoglobin (Hb) content and packed cell volume (PCV) were gradually increased significantly (p<0.01 and p<0.05) in cattle. Conversely, the total leukocyte count (TLC) were decreased significantly (p<0.01 and p<0.05) in treated cattle. The alanine aminotransferase (ALT) and aspartate aminotransferase (AST) level were not significantly changed in the cattle. The body weight was increased significantly (p<0.01 and p<0.05) in barbados lilac, pineapple and Benazol® treated cattle.In contrast, body weight was decreased in control group. The present study reveals that water extracts of barbados lilac leaves were moderately effective and pineapple leaves were relatively less effective against mixed gastrointestinal nematode infections in cattle. DOI: http://dx.doi.org/10.3329/pa.v19i1.17107 Progress. Agric. 19(1): 51 - 59, 2008